2018
DOI: 10.1038/s41374-018-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear shape and orientation features from H&E images predict survival in early-stage estrogen receptor-positive breast cancers

Abstract: Early-stage estrogen receptor-positive (ER+) breast cancer (BCa) is the most common type of BCa in the United States. One critical question with these tumors is identifying which patients will receive added benefit from adjuvant chemotherapy. Nuclear pleomorphism (variance in nuclear shape and morphology) is an important constituent of breast grading schemes, and in ER+ cases, the grade is highly correlated with disease outcome. This study aimed to investigate whether quantitative computer-extracted image feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 29 publications
5
84
1
Order By: Relevance
“…Quantification of nuclear components represented the following characteristics: cell nuclei were smaller, with lower chromatin in noncancerous tissues, while cancer cells exhibited greater heterogeneity, probably due to genetic or epigenetic alterations, together with high nuclear density related to differentiation states (Figure ). By microscopic diagnosis, it has been shown that nuclear abnormality is a fundamental hallmark of tumor cells and an indicator of patient outcomes in many cancer types . Observations of tissue structural atypia are essential for pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of nuclear components represented the following characteristics: cell nuclei were smaller, with lower chromatin in noncancerous tissues, while cancer cells exhibited greater heterogeneity, probably due to genetic or epigenetic alterations, together with high nuclear density related to differentiation states (Figure ). By microscopic diagnosis, it has been shown that nuclear abnormality is a fundamental hallmark of tumor cells and an indicator of patient outcomes in many cancer types . Observations of tissue structural atypia are essential for pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…By microscopic diagnosis, it has been shown that nuclear abnormality is a fundamental hallmark of tumor cells and an indicator of patient outcomes in many cancer types. 46,47 Observations of tissue structural atypia are essential for pathological diagnosis. However, our findings supported that nuclear shape may also be related to the differentiation grades of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal nuclear shape is a pathognomonic trait that has been used as a diagnostic indicator of human disease for nearly a century, albeit without an understanding of the mechanisms of nucleus deformations and their effects on function. Cancer diagnostic assays examine cell nuclei for unusual sizes and shapes via Pap smear (cervical) [16], nuclear herniations termed "blebs" that correlate with Gleason score (prostate) [17], and aberrant shapes and orientations via quantitative histomorphometrics (breast) [18,19]. Aberrantly shaped nuclei also occur in mechanically demanding environments, such as muscle cells in heart disease (cardiomyopathy) associated with progeria and aging and muscular dystrophy [20].…”
Section: Physiological Impact Of Defects In Nuclear Shape and Mechanicsmentioning
confidence: 99%
“…Many recent researches focus on mining quantitative morphological features from diagnostic pathology slides, which has been proved to be an effective way to alleviate the intra-observer and inter-observer variability, by analyzing digital pathology images in context of cancer grading [17,18], risk stratification [19][20][21][22], and tumor outcomes prediction [20,21,[23][24][25][26]. Wang et al [19] presented an image classifier using nuclear orientation, texture, shape and tumor architecture to predict disease recurrence in early stage non-small cell lung cancer from digitized H&E images.…”
Section: Introductionmentioning
confidence: 99%